The Effect of Anti-seizure Drugs on Visual Functions in Epilepsy Patients - Pınar Bengi Boz; Deniz Tören (Archives of Epilepsy)
Objective: In this study, we aimed to detect early signs of central nervous system involvement in patients with epilepsy, under anti-seizure drug monotherapy, using visual evoked potentials (VEPs), a non-invasive and easily applicable test, and to correlate these findings with clinical data. Methods: Between June 10, 2023, and December 31, 2023, 64 patients with epilepsy aged 18 to 65 who had been receiving monotherapy for at least 6 months were included in the study. Additionally, 50 age- and gender-matched healthy individuals were included as a control group. Age, gender, anti-seizure medication, and duration of use, ophthalmologic and neurologic examination findings, and brain magnetic resonance imaging results were recorded. Informed consent was obtained from all participants. VEPs of both groups were studied. Results: The mean age of the patients was 32.39±12.78 years; 51.6% were female, and 48.4% were male. The distribution of medications among the patients was as follows: 59.4% were using levetiracetam, 25% valproic acid, 10.9% lamotrigine, 3.2% carbamazepine, and 1.5% lacosamide. The N75 and P100 latencies and amplitudes in patients were significantly higher than those in the control group (p<0.05). P100 latency differences in levetiracetam, carbamazepine and lacosamide users were less pronounced compared to valproic acid and lamotrigine users; however, these differences were not statistically significant (p>0.05.). Conclusion: In this study, levetiracetam, lacosamide, and carbamazepine were found to have less adverse effects on P100 latency, independent of the duration of treatment. For the early diagnosis and treatment of silent visual disturbances, epilepsy patients should undergo visual evoked potential and eye examinations at regular intervals.